Empowering Chinese college students in English as a foreign language writing classes: Translanguaging with translation methods - Zhang, Limei (Frontiers in Psychology, 2023)
Learning activities based on translation has attracted increasing attention among researchers in English as a Foreign Language (EFL) teaching and learning under the influence of translanguaing pedagogies. This study was designed to examine the effect of translation methods as pedagogical tools on students’ writing performance in EFL classrooms. 89 Chinese college students participated in the study. They were required to complete tests of essay writing before and after the use of the translation method. Nine students were invited to attend an interview after the writing test. Results showed that the students improved their essay writing performance significantly after the translation method. The participating students’ confidence and interest in essay writing were also enhanced. Findings from the study have important implications for effective writing instruction for Chinese EFL college students.